How I became homeless: Stories of homeless shelter residents in El Paso, Texas USA (Journal of Comparative Social Work, 2020)
This study explores the stories of 40 homeless residents from a local shelter in El Paso, Texas located in the United States, with an emphasis on the socio-ecological factors (i.e. individual and environmental) leading to their homelessness. A total of 40 adult residents were recruited using purposive sampling between 2016 and 2017 to participate in an in-depth interview and a brief survey. Interview data were analysed using grounded theory method. Survey data were presented in the form of descriptive statistics. Overall, we found that contrary to the typical stereotypes that attribute the difficulties the homeless population faces to personal deficits (e.g. lack of motivation for upward mobility and maladaptive coping), many of our participants struggled with varying personal challenges and social constraints, which created a vulnerability to homelessness. Furthermore, inconsistent with the assumption that Hispanics are less susceptible to the concern of homelessness given their cultural and family orientations, we found that among our participants who were Hispanic, more than half had contact with family or friends and/or had at least one family member who was homeless, thus indicating that Hispanics are not free from the challenge of homelessness. This finding has public policy implications for U.S. cities that are predominantly Hispanic (of which El Paso is one), and cautions about the danger of overgeneralizing the homeless population. We noted five major life domains (legal, relational, economic, physiological, and psychiatric) that triggered the participants’ homelessness. Understanding factors leading to homelessness can form the basis for formulating effective intervention programmes that promote well-being, as well as a holistic roadmap that prioritizes strategies for sustainable healthy living.